Family composition and transitions into long-term care services among the elderly - Astri Syse; Alyona Artamonova; Michael J. Thomas; Marijke Veenstra (Statistics Norway, Research Department, 2021)
Elderly's use of long-term care (LTC) services are likely to be influenced by family members, but there is scarce research on the role played by partners and/or adult children, especially taking geographic proximity into account. We thus examine how partners and adult children influence elderly's LTC use, taking regional differences into account. We employ logistic discrete-time hazard regression models on linked registry data for complete cohorts of elderly individuals (65+ years), their partners, their adult children, residing in Norway in the period 2010-2016 (N=820 000). We also include municipal characteristics. One's own, partner's and child(ren)'s characteristics are all associated with elderly individuals' LTC use. Partners' resources matter the most, but those of adult children are relevant when partners are less resourceful or absent. Childless elderly use more LTC services than elderly with children, and elderly with resourceful children living nearby use the least LTC services. The trends are similar across municipalities, but the magnitudes vary slightly depending on their geographic location and sociodemographic and economic resources. Future demographic and economic changes warrant a better understanding of the role played by family members for elderly's use of LTC services.
Keywords: I10; I12; I18; J10; H41; 330; Care use; Family; Formal care; Geographic; Informal care; Long-term care (LTC)